PENGARUH INDEPENDENSI, KOMPETENSI, PENGALAMAN KERJA, PENDIDIKAN, PERBEDAAN GENDER, DAN INTEGRITAS AUDITOR TERHADAP PROFESIONALISME AUDITOR BPK RI PERWAKILAN PROVINSI JAMBI - Jimmy Mardi Siregar; Desmiyawati '; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to examine the effect of the influence of independency, competency, work experience, education, gender difference, and auditors integrity to professionalism of BPK RI’s auditors especially those who are working in auditing firm representative Jambi province. Professional auditor is the auditor who acknowledges its responsibility towards society, the responsibility of the client, the responsibility towards colleagues included to behave respectable, though this is a personal sacrifice. Methods of data collection in this study is a method of questionnaire instruments that are delivered directly to the auditing firm representative Jambi province though the people work who work in community relations. Population in this study is BPK RI’s auditors who worked in a auditing firm representative Jambi province. The entire population to be sampled by the researches. The number of samples used in this study were 33 people who worked in auditing firm representative Jambi province. Methods of analysis is conducted with a multiple regression analysis version 20,00 for windows. The results for testing that has been done. Practical regression F ( F Test ) showed that the auditor’s competency, education, and integrity had a influences toward auditor professionalism. Analysis using the coefficient of determination ( R2 ) found that the contribution of the influence of the independent variable on the dependent variable is 81,3 % while the remaining 18,7% is influenced by other variables not included in this study.Keywords : Professionalism, Independency, Competency, and Auditors Integrity.